Professional development for teachers of nursing students for whom English is an additional language: A reflection on practices. (July 2019) - Havery, Caroline; Townsend, Lisa; Johnson, Anna; Doab, Anna
Abstract: The increasing linguistically and culturally diverse cohort of university students in nursing degree programmes has resulted in a plethora of approaches to address issues related to English language, academic writing and professional communication. Approaches that integrate language development within core nursing subjects are usually regarded as effective, as they offer students opportunities to be socialised into the language of their specific discipline areas. However, developing and implementing an integrated model can be challenging and many discipline academics feel unprepared to address language issues within the curriculum. This paper discusses a pilot project where we, a language academic and a group of nursing academics, adopted a clinical supervision model to problematise subject content and pedagogic practices. The aim was to enable English as additional language students better transition to Australian university studies by integrating an explicit focus on language development within the subject content. The paper outlines the model and draws on our reflections to discuss outcomes. These included changes to subject content and pedagogic practices, as well as increased confidence of nursing academics to teach in ways that have been found to be effective for English as additional language students. Highlights: English as additional language students may need academic language development. Nursing academics may lack confidence in providing language development. A clinical supervision model was used to provide professional development. This model led to changes in pedagogic practices and subject content.